PROCESSING AND MICROSTRUCTURE OF LACRO3 THIN FILM DERIVED FROM CHELATING PRECURSORS - Lu X.C.; Xu T.X.; Dong X.H. (My University, 2000)
LaCrO3 thin films were successfully prepared at lower temperatures by the sol-gel process based on organic chelating precursors. The formation and transition of the gel derived from the chelate solution were analyzed by means of IR, DTA-TG, XRD and TEM. In addition, the formation and microstructure of thin films were investigated by SEM and XRD. The results show that the gel formed by the condensation reaction is decomposed at about 195 °C, transformed into a great quantity of LaCrO3 by heat-treating at 200 °C for 1 h, and the complexing ways in the gel have an important influence upon the formation of LaCrO3. The formation process of thin film includes the nucleation and growth on the substrate, the formation of polycrystalline islands and the continuous film by repeating the dip-coating process. Higher heat-treatment temperature gives rise to larger granules in the thin film.